Association between professional burnout and cortisol changes in health professionals: A systematic review (Research, Society and Development, 2023)
Introduction: Professional burnout is a disorder in which professionals are exhausted. Symptoms such as excessive tiredness, frequent headache, insomnia, gastrointestinal and mood disorders, and changes in blood pressure are some symptoms that can lead to Burnout Syndrome. Health professionals come into direct contact with stressors, so they are vulnerable. Based on this, the study seeks to assess whether there is a relationship between professional exhaustion and the increase in cortisol, secreted by the body under stressful conditions. Objective: To analyze the association between professional burnout and changes in cortisol levels in health professionals. Methods: articles selected from electronic research databases between January and February 2023, with no time restriction and in English. After screening and eligibility, three articles were included for evaluation. Results: There is a scarcity of literature to measure stress conditions in this investigation, 40% of the studied population had cortisol values ​​outside the healthy reference range and professionals in direct contact with patients have high cortisol levels. Discussion: Professionals who directly treat patients have higher cortisol levels due to contact with stressors at work and there is still a lack of studies on changes in cortisol levels. Conclusion: direct contact with patients produces an increase in cortisol.